2021
DOI: 10.1200/jco.20.00555
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Follow-Up of Ibrutinib Monotherapy in Symptomatic, Previously Treated Patients With Waldenström Macroglobulinemia

Abstract: PURPOSE We report the long-term findings and final analysis of a pivotal multicenter trial of ibrutinib monotherapy in previously treated patients with Waldenström macroglobulinemia (WM). PATIENTS AND METHODS Sixty-three symptomatic patients with median prior therapies of two (range, one to nine therapies), of whom 40% were refractory to their previous therapy, received ibrutinib at 420 mg/d. Dose reduction was permitted for toxicity. RESULTS The median follow-up was 59 months, and overall and major response r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
152
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 116 publications
(160 citation statements)
references
References 35 publications
7
152
1
Order By: Relevance
“…1,2 The presence of mutated MYD88 is associated with a decreased risk of histological transformation, longer overall survival, and sensitivity to ibrutinib. 3,4 Over 40 nonsense and frameshift CXCR4 variants have been identified in WM patients. 5,6 Nonsense CXCR4 S338X variants are the most common, occurring in 50% of WM patients due to C > A or C > G nucleotide transversions.…”
Section: Mutations In Waldenström Macroglobulinemiamentioning
confidence: 99%
“…1,2 The presence of mutated MYD88 is associated with a decreased risk of histological transformation, longer overall survival, and sensitivity to ibrutinib. 3,4 Over 40 nonsense and frameshift CXCR4 variants have been identified in WM patients. 5,6 Nonsense CXCR4 S338X variants are the most common, occurring in 50% of WM patients due to C > A or C > G nucleotide transversions.…”
Section: Mutations In Waldenström Macroglobulinemiamentioning
confidence: 99%
“…However, no clear drug was found after searching published literatures and from our experience. According to the patient's preference, ibrutinib single treatment was initiated, which may be bene cial for the primary disease as well as secondary ITP and AIHA [14][15][16] . As expected, the thrombocytopenia was quickly resolved, and became transfusion independent, but the AIHA did not resolved and even worsen, which further indicated that the AIHA was not WM-related.…”
Section: Discussionmentioning
confidence: 99%
“…10 Ibrutinib monotherapy was highly active with an overall response rate (ORR) of 91%, major response rate (MRR) of 79%, and very good partial response rate (VGPR) of 30% with prolonged follow-up. 10,11 Responses to ibrutinib were durable with an estimated 5-year progression-free survival (PFS) and overall survival (OS) of 54% and 87%, respectively. A notable finding was the impact of MYD88 and CXCR4 mutations on ibrutinib outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Patients wildtype (WT) for both MYD88 and CXCR4 had no major responses and a median PFS of 5 months to ibrutinib. [10][11][12] Among patients with mutated MYD88, the concurrent presence of a CXCR4 mutation adversely impacted response rates, response kinetics, and 5-year PFS (38% vs. 70%). 10,11 Similar outcomes to ibrutinib monotherapy have been reported in phase 2 trials of treatment-naïve (n=30) and rituximab-refractory WM patients (n=31), as well as in the recent phase 3 ASPEN trial (n=199) comparing ibrutinib to zanubrutinib.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation